Pengaruh Pemberitaan Kasus Bank Century Di Televisi Terhadap Pembentukan Kognisi Opini Publik Di Kota Manado Propinsi Sulawesi Utara - Kalangi, Johnny Semuel (JURNAL ADMINISTRASI BISNIS, 2014)
The title of this study is "The Effect of Bank Century case reports on television (Metro TV and TV One) to the formation cognitive of public opinion in Manado City, North Sulawesiâ. This study was conducted with a mass communication approach that used the television to shape public opinion. The purpose of this research is to know the influence of television is everywhere, the repetition of news, uniformity and conformity with the news public opinion on television (Metro TV and TV One) against the formation of knowledge, beliefs and perceptions case decisions results of Bank Century in the city of Manado in North Sulawesi Province. As for the theory used is Cognitive Psychology (Grand theory), Stimulus-Organism-Response (Mid Range Theory), The Spiral Of Silence (Application Theory). The research method uses explanatory survey, by distributing questionnaires that consist of 9 questions of respondent data and 45 statements of research data variables X and Y to 190 respondents. The sampling process uses Multy Stage Cluster Sampling, while the data process uses Path Analysis. The results indicated that the availability of television is everywhere,the repetition news, news uniformity and conformity of public opinion are very influential / significant to the formation of knowledge, beliefs, perceptions, feelings, judgments, willingness to accept, willingness to express, discussion, agreement, and behavior in Manado City North Sulawesi. Keywords:Bank Century case reports, television, cognitive of public opinion